Re-bordering the Economy: The Return of Territorial Sovereignty in Economic Governance - Abdelaziz Abdalla Alowais (Journal of Informatics Education and Research, 2025)
This study explores the resurgence of territorial sovereignty in economic governance, specifically at the rise of the phenomenon of 'economic rebordering,' which began after 2016. In the context of decades of globalization, however, the rise of recent political realignments, such as the Trump administration’s 'America First' policy agenda, has devolved national control of economic policy, trade, and investment. The study explores how sovereignty evolves from traditional political or military definition into the essence of economic autonomy and regulatory control. The study is a demonstration using content analysis of key U.S. policy documents, media narratives and think tank publications, that economic sovereignty–primarily conceptualized as a reliance on domestic sources for critical inputs and membership in comparative advantage production chains as the new primary axis of national power and is institutionalized through mechanisms such as tighter foreign direct investment reviews, domestic production mandates and digital trade barriers. The study combines three intellectual strands, geo-economics, sovereignty theory, and new institutionalism, to offer a nuanced explanation of how states strategically redefine sovereignty discourse and governance structures to address global economic challenges. The study shows a dramatic ideological and practical turn with far-reaching consequences, both for multilateralism and the future of international cooperation.